Odprta oblika in njen odmev v slovenski glasbi - Rihtaršič, Urška (Muzikološki zbornik, 2018)
The article deals with the open form and tries to uncover its features by examining a number of representative compositions. Theoretical texts published by the composers along with their pieces of music serve as the foundation of the analysis. Based on these findings, the article subsequently focuses on the open form in the work of the younger generation of Slovenian composers of the first post-war era and attempts to explain its specifics in the light of social developments.
Keywords: konceptualna mobilnost; moment; odprta oblika; Pro Musica Viva; slovenska glasba